2005
DOI: 10.1144/0060187
|View full text |Cite
|
Sign up to set email alerts
|

The Lower Cretaceous plays of the Central and Northern North Sea: Atlantean drainage models and enhanced hydrocarbon potential

Abstract: Int he CentralNorthS ea, the Apto-Albianp layappears to be confined to patchyareasw ithint he MorayFirthb asins. Int hisarea, itisw idely believed reservoir-quality sandsw eresourced from localr esidual LateCimmerianhighs,withresultant limited distributions ofcommercialfairways. Localhydrocarbon modelling provest hatm ost hydrocarbons discovered to dateoccur withins tratigraphic traps,d iscovered largely by serendipity duringa ppraisalo folders tructurallydefined reservoirs. Re-appraisalo fJ urassic to Cretace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…Elsewhere in the northern North Sea, K2 times were associated with the development of the Sola and Agat sandstones, which have been ascribed to tectonism linked to North Atlantic rifting during the Aptian and Albian (Fig. 2) (Skibeli et al, 1995;Oakman and Partington, 1998;Brekke et al, 2001;Bugge et al, 2001;Copestake et al, 2003;Oakman, 2005). In the North Viking Graben, however, no evidence of such tectonism has been found.…”
Section: Controls On the Temporal Evolution Of Early Post-rift Deposimentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere in the northern North Sea, K2 times were associated with the development of the Sola and Agat sandstones, which have been ascribed to tectonism linked to North Atlantic rifting during the Aptian and Albian (Fig. 2) (Skibeli et al, 1995;Oakman and Partington, 1998;Brekke et al, 2001;Bugge et al, 2001;Copestake et al, 2003;Oakman, 2005). In the North Viking Graben, however, no evidence of such tectonism has been found.…”
Section: Controls On the Temporal Evolution Of Early Post-rift Deposimentioning
confidence: 99%
“…It has been established that rifting ceased in the northern North Sea during the Volgian (Johnson, 1975;Faerseth et al, 1995;Faerseth and Ravnås, 1998;Faerseth and Lien, 2002;Zachariah et al, 2009). The basin then underwent post-rift thermal subsidence (Badley et al, 1984;Gabrielsen et al, 1990;Prosser, 1993;Nøttvedt et al, 1995;Gabrielsen et al, 2001) and was affected by relative changes in sealevel, in association with the far-reached effects of renewed North Atlantic rifting and the Austrian Orogeny during the Aptian (Skibeli et al, 1995;Brekke et al, 2001;Bugge et al, 2001;Kjennerud et al, 2001;Kyrkjebø et al, 2001;Copestake et al, 2003;Oakman 2005). Fig.…”
Section: Regional Settingmentioning
confidence: 99%
“…The overall deepening trend during the Cretaceous meant that a marine sedimentary environment prevailed, and hemipelagic clay was the dominant lithology deposited in the basins (Fig. Conversely, periods of transgression and highstand saw a decrease in clastic sediment deposition and a return to the dominant deposition of hemipelagic clay in basinal areas, whereas carbonate deposition was favoured around the submerged structural highs and on the shelfal areas (Skibeli et al, 1995;Brekke et al, 2001;Bugge et al, 2001;Oakman, 2005) (Fig. However, during relative lowstands, de¢ned by published sea-level and chronostratigraphic studies (Haq et al, 1988), clastic sediments derived from the structurally high areas were deposited in the basins.…”
Section: Geological Settingmentioning
confidence: 99%
“…3). These episodes are dominantly associated with the onset of the Austrian orogeny and North Atlantic rifting that initiated in Aptian times but, on the whole, tectonic activity and associated extensional faulting are considered to have diminished greatly from the Late Jurassic into the Cretaceous (Copestake et al, 2003;Oakman 2005) (Fig. 3).…”
Section: Geological Settingmentioning
confidence: 99%
“…Simulation studies of CO 2 injection identified the storage capacity of the Captain Sandstone to be between 358 and 2495 Mt (Jin et al 2012). As the injection of CO 2 is reliant on the displacement of existing pore fluids, large-scale injection results in increased pore-fluid pressure, the effects of which will be felt across large areas in well-connected aquifer systems (Chadwick et al 2009b;Jin et al 2012;Noy et al 2012).…”
mentioning
confidence: 99%